2015
DOI: 10.3390/v7122958
|View full text |Cite
|
Sign up to set email alerts
|

What Can We Learn from a Metagenomic Analysis of a Georgian Bacteriophage Cocktail?

Abstract: Phage therapy, a practice widespread in Eastern Europe, has untapped potential in the combat against antibiotic-resistant bacterial infections. However, technology transfer to Western medicine is proving challenging. Bioinformatics analysis could help to facilitate this endeavor. In the present study, the Intesti phage cocktail, a key commercial product of the Eliava Institute, Georgia, has been tested on a selection of bacterial strains, sequenced as a metagenomic sample, de novo assembled and analyzed by bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 36 publications
0
35
1
Order By: Relevance
“…If multiple phages are amplified in a batch culture, it is possible that a ‘winner’ phage is amplified more efficiently and predominates the lysate, with less efficiently replicating phages representing low coverage phages. Previous investigations into the Eliava Intestiphage cocktails revealed that sequences detected with a low coverage were nevertheless biologically active and easily detected by infection assays (Zschach et al ., ; McCallin et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If multiple phages are amplified in a batch culture, it is possible that a ‘winner’ phage is amplified more efficiently and predominates the lysate, with less efficiently replicating phages representing low coverage phages. Previous investigations into the Eliava Intestiphage cocktails revealed that sequences detected with a low coverage were nevertheless biologically active and easily detected by infection assays (Zschach et al ., ; McCallin et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…If multiple phages are amplified in a batch culture, it is possible that a 'winner' phage is amplified more efficiently and predominates the lysate, with less efficiently replicating phages representing low coverage phages. Previous investigations into the Eliava Intestiphage cocktails revealed that sequences detected with a low coverage were nevertheless biologically active and easily detected by infection assays (Zschach et al, 2015;McCallin et al 2013). Without metagenome sequencing or indicator strains for the detection of each specific ingredient phage, it will be difficult to maintain a constant ratio of ingredient phages in the cocktail -a likely regulatory requirement for medicinal products in the West.…”
Section: Discussionmentioning
confidence: 99%
“…The Eliava Institute in Tbilisi, Georgia has in particular been dominant in this regard and produce cocktails containing a mixture of phages for a range of bacterial infections. One of the steps towards adopting phage therapy in the West, is likely to be a full characterization of the content of these cocktails, which due to the way they are manufactured is not known [ 38 ]. Further, the current approach to exploration of many ecological niches is done by untargeted sequencing of samples isolated directly from the environment, so called metagenomics.…”
Section: Introductionmentioning
confidence: 99%
“…Phage products such as Pyophage and Intestiphage are examples of modifiable cocktails that are still in use today in Georgia and Russia. Metagenomic analysis of these products indicates they are complex mixtures of phages [38][39][40]. This complexity combined with the periodic changes in composition means these products are not directly suited to a traditional regulatory drug development pathway such as the US FDA has established.…”
Section: Approaches For Phage Therapeutic Designmentioning
confidence: 99%